An ethnobotanical study in Midyat (Turkey), a city on the silk road where cultures meet - Ali Akgul; Ayfer Akgul; Serdar G. Senol; Hasan Yildirim; Ozcan Secmen; Yunus Dogan (BMC, 2018)
Abstract Background Studies of ethnobotanical usages in south-eastern Turkey are rare. To widen this field of knowledge, we conducted an ethnobotanical study in Midyat (Mardin Province), Turkey. Methods The field study was completed during three years (2007-2010). Our aim was to document the ethnobotanical uses of local plants and to make an ethnobotanical inventory of uncommon plants using qualitative interviews. Results During field studies, 368 voucher specimens were collected in the investigated area. Ninety-two traditionally used plant species were reported from Midyat and surrounding vicinities in Turkey. Among the 92 taxa (129 usages), 35% were used for medical purposes, 22% for food, 13% for animal fodder, 7% as ornamental plants and dyes, 6% as brooms, 4% for latex and as fragrance, 4% for herbal tea, molasses and wine preparation, 3% for agricultural purposes, and 6% for other purposes. Comparative assessment showed that Teucrium polium (0.51), Matricaria aurea (0.26), Alcea setosa (0.21), and Malva neglecta (0.21) have the highest recorded UVs, and the following taxa had UVs between 0.10-0.20: Anthemis cotula (0.12), Allium cepa (0.13), Alcea striata subsp. striata (0.14), Crupina crupinastrum (0.12), Papaver rhoeas (0.13), Salvia multicaulis (0.14), Thymbra spicata (0.11), and Vicia pannonica subsp. striata (0.15). We reported the ethnobotanical usages of 21 taxa for the first time, in addition to indicating usages previously recorded in the literature. We also recorded four endemic plant usages in the area: Alkanna trichophila var. mardinensis, Centaurea kurdica, Centaurea stapfiana, and Sideritis libanotica subsp. linearis. They have variable leaf and flower morphology that are used traditionally. They are present as well-developed populations and thus their conservation status is not compromised. Additionally, Thymbra sintenisii is a recorded species that is classified as a rare and extensively used species in the region. Conclusions These results contribute to the fundamental knowledge of ethnobotanical usages in Midyat. To date, ethnobotanical studies have not been carried out in this region. This investigation uncovered usages of endemic medicinal plant species and traditional knowledge of Midyat communities living in a mixed culture. The people of Midyat, Batman, and Şırnak are Turkish citizens from various ethnic backgrounds, such as Kurdish, Arabic, and Syriac. We compared our data with results from other studies conducted in Turkey, particularly in south-eastern and eastern regions, as well as with studies from bordering countries, Iraq, Jordan, Syria, and Iran. Nonetheless, more work needs to be conducted to extend the present knowledge for locals to contribute to and evaluate economic potential in the region.